Archaeology and rapid climate changes - Budja, Mihael (Documenta Praehistorica, 2015)
The "rapid climate change", "cycles of abrupt climate shift", and "cold events" in the Holocene are discussed in relation to the "collapse of civilisation" concept, and adaptive cycles and the panarchy interpretative model.
Keywords: archaeology; arheologija; climate; klimatske spremembe; podnebje; prazgodovina